EFFECTIVENESS OF WORD SQUARE MEDIA ON ARABIC VOCABULARY: AN EXPERIMENTAL STUDY OF SERI ABIM STUDENTS IN SELANGOR, MALAYSIA - Fikri alhamdi; Hanomi, Hanomi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Arabic vocabulary instruction in elementary schools is still largely dominated by conventional approaches that emphasize memorization, resulting in limited student engagement. This condition contributes to low mufradāt mastery and weak learning motivation. This study aims to examine the effectiveness of Word Square media in improving students’ Arabic vocabulary mastery. A quantitative approach was employed using a quasi-experimental one-group pre-test–post-test design, conducted with third-grade students at SERI ABIM Elementary School, Selangor, Malaysia. Data were collected through pre-test and post-test instruments and analyzed using statistical tests with SPSS. The findings indicate that the use of Word Square media has a significant effect on improving students’ Arabic vocabulary mastery. This media enhances learning engagement, visual memory, and structured vocabulary comprehension in a more enjoyable learning environment. These findings are expected to provide empirical reference for the development of Arabic vocabulary instruction in Indonesia, particularly in promoting the use of Word Square media as an effective and contextual alternative for elementary school learning.